Unlocking Sustainable Horizons: Integrating Solar Cell Radio Wave Technology with AI for Business Advancement in Vaccine and Antibiotic Sectors - Chen jin Kim (BULLET : Jurnal Multidisiplin Ilmu, 2023)
This review paper provides an extensive examination of the synergistic integration of several technologies, such as radio waves, solar cell technology, artificial intelligence (AI), business information technology (IT), immunizations, and antibiotics, with the goal of fostering sustainable innovation. Comprehensive analysis is carried out, highlighting the manner in which healthcare solutions, renewable energy, and smart technologies are connected. The abstract looks at how technology may advance by using radio waves and solar cells, and how artificial intelligence and corporate IT could maximize productivity. The evaluation also explores the novel ways in which vaccinations and antibiotics might revolutionize public health. By connecting various fields, the article aims to offer insights into the all-encompassing and sustainable strategy that results from the convergence of numerous technologies for the benefit of business and society. This research explores the intricate connections between solar cell technology and artificial intelligence (AI), elucidating how the convergence of advanced computational capacity and renewable energy sources propels innovations never seen before. In order to optimize productivity and decision-making processes, business IT plays the critical role of facilitator, orchestrating the seamless integration of disparate technologies. The important topic of medicine is also covered in the article, where immunizations and antibiotics are critical for creating resilient societies. This study explains how combining these technological and medical advancements together may lead to comprehensive and sustainable solutions, while also emphasizing the need of multidisciplinary collaboration in tackling the challenges of our rapidly changing environment.